Study About Pathogenic Bacteria Associated With Bovine - AL-Taan, Safana A. S.; AL-Jobori, Asmaa H.; AL-Bana., Anton S. (The Iraqi Journal of Veterinary Medicine, 2004)
Out of 100 raw milk samples collected from one hundred cows infected with mastitis, thirty three isolates of different types of pathogenic bacteria were isolated using different types of selective media. On the basis of traditional bacteriological tests, these isolates were identified as the following: 13 isolates of Staphylococcus aureus, 9 isolates of B-haemolytic Streptococci, 6 isolates of Coliform bacteria, 4 isolates of Corynebacterium pyogenes, and only one isolate Bacillus cereus. In addition to these isolates, a number of non-pathogenic bacteria were recovered during the isolation and they were considered as contaminants of milk such as S. epidermidis, C. bovis and B. subtilus. The total number of living bacteria present in milk samples was measured and it was ranged from (1400 to 1800) bact./ml. The isolates of pathogenic bacteria were tested for their sensitivity to different types of antibiotics and the results were: 100% of these isolates were sensitive to Gentamycin and Tetracycline, 11 (84.6%) isolates of S. aureus, 6(66.2%) isolates of B-hacmolytic Streptococci , 4(66.2%) isolates of Coliform bacteria and 3(75%) es of C. pyogenes were sensitive to Ampicillin, Penicillin, Erythromycin and Cepholexin. While Bacillus cereus isolate was resistant to all these antibiotics. As a result of this work, generally the bacteriological quality of this milk is acceptable due to the low number of viable count of bacteria in milk and the isolates showed high level of sensitivity to the antibiotics used in this study.